TRANSFORMATION OF THE SYMBOLIC MEANING OF THE MAYANG TWINS IN THE TRADITIONAL WEDDING RITUAL OF CENTRAL JAVA IN PISANG INDAH VILLAGE, BUMI AGUNG DISTRICT, WAY KANAN, LAMPUNG - Nurhidayah Putri; Sudarman Sudarman; Muhtadin Muhtadin; Muslimin Muslimin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This study investigates spiritual transformation within the Mayang Twins tradition as practiced in the Central Java wedding ritual in Pisang Indah Village, Way Kanan, Lampung. The research aims to identify shifts in symbolic meaning and the underlying factors influencing these changes within the migrant community context. Employing a qualitative methodology grounded in religious anthropology, primary data were gathered through participatory observation, document analysis, and in-depth interviews with key informants. The analysis reveals a process of desacralization, whereby the Mayang Twins' role has shifted from a sacred medium of cosmic-spiritual communication to a decorative element valued primarily for its visual prestige. This transformation is attributed to internal factors, such as the stagnation in the intergenerational transmission of philosophical knowledge, and external factors, including the influence of rapid modernization and cultural adaptation strategies aligned with Islamic values. The study concludes that the tradition's spiritual essence has diminished, despite the preservation of its physical form. It is recommended that the Village Government and the local Cultural Office establish communal cultural spaces, such as annual festivals or digital pocket books on traditional philosophy, to revitalize cultural understanding among younger generations and sustain Javanese identity within the diaspora.